2018
DOI: 10.1108/jm2-12-2016-0127
|View full text |Cite
|
Sign up to set email alerts
|

Metrics of product modularity: lessons learned from case companies

Abstract: Purpose Modular product development is a turning table concept in terms of benefits and impact in manufacturing companies. It offers added benefits to the companies with respect to reduce lead-time, improve assemble ability and agility in supply chain management, promote product family and enhance customer satisfaction. This paper aims to identify the patterns of modular product development strategy by using measurement techniques. Design/methodology/approach Both quantitative and qualitative approaches are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…This approach is mainly used in the industrial environment in the concept phase of vehicle design. Publications with a strong industrial reference from the recent past include Shamsuzzoha et al, which have summarized lessons learned on modular development from six industrial partners (Shamsuzzoha et al 2018), as well as Mortensen et al, which have identified the following success factors for implementing the module strategy in companies: the company must aim big and be willing to change its foundation accordingly, draw on the right positional strength and have broad organizational inputs, and properly coordinate work and then actively seek to preserve the focus and results over a long period of time (Mortensen et al 2018).…”
Section: Methods For Modularization and The Development Of Modular Kitsmentioning
confidence: 99%
“…This approach is mainly used in the industrial environment in the concept phase of vehicle design. Publications with a strong industrial reference from the recent past include Shamsuzzoha et al, which have summarized lessons learned on modular development from six industrial partners (Shamsuzzoha et al 2018), as well as Mortensen et al, which have identified the following success factors for implementing the module strategy in companies: the company must aim big and be willing to change its foundation accordingly, draw on the right positional strength and have broad organizational inputs, and properly coordinate work and then actively seek to preserve the focus and results over a long period of time (Mortensen et al 2018).…”
Section: Methods For Modularization and The Development Of Modular Kitsmentioning
confidence: 99%
“…Modular product development strategy also depends on the customization level. More customization triggers more modularity and vice versa (Silveira et al, 2001;Zhang et al, 2014;Shamsuzzoha et al, 2018).…”
Section: F4 Customization Levelmentioning
confidence: 99%
“…The component interface has a direct impact on product modularity. Properly designed component interface contributes to promoting product modularity (Gershenson and Prasad, 1997;Shamsuzzoha et al, 2018).…”
Section: F16mentioning
confidence: 99%
See 2 more Smart Citations